ANALISIS DINAMIKA EKSPOR DAN KEUNGGULAN KOMPARATIF MINYAK KELAPA SAWIT (CPO) DI INDONESIA (ANALYSIS OF EXPORT DYNAMICS AND COMPARATIVE ADVANTAGE OF INDONESIAN CRUDE PALM OIL) - AGUSTIAN, ADANG; U. HADI, PROJOGO (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 3 November2004, 2012)
Crude Palm Oil (CPO) has been one of important agricultural export commodities of Indonesia, but it faces competition with product from other exporting counties as well as trade barriers from importing countries. This study aims to analyse changes in export and comparative and competitive advantage as indicators of Indonesian palm oil competitiveness. By employing trend and DRCR (Domestic Resource Cost Ratio) and PCR (Private Cost Ratio) methods, it is concluded that : (1) Quantity and value of Indonesian palm oil export, especially CPO (Crude Palm Oil) during 1996-2001 increased respectively by 19.91% and 1.52% per annum, namely from 1.67 million tons and US$ 0.83 billion in 1996 to 4.90 million tons and US$ 1.08 billion in 2001; (2) Most Indonesian CPO was exported to India (17.90%), the Netherlands (14,29%) and China (7.14%); (3) Domestic distribution of palm oil was controlled by the government aimed at maintaining the balance between the filling of the domestic demand and the foreign exchange creation; (4) Trade policy in some major importing countries remains protective, namely imposition of high tariff, quota and health issues; and (5) Oil palm farm in Indonesia has a comparative as well as competitive advantage indicated by the DRCR and PCR coefficients of less than unity. It is suggested that oil palm needs to be continuously developed in Indonesia while attempting in various WTO forum for more opened and fairer trade of palm oil.
Keywords: Exports, Comparative Advantage, Crude Palm Oil (CPO)